A pillar of community: Local newspapers, community capital, and impact on readership and advertising. Issue 5 (20th October 2018) - Yun, Gi Woong; Morin, David; Ha, Louisa; Flynn, Mark; Park, Sanghee; Hu, Xiao
ABSTRACT: With the advent of the Internet, once prosperous local newspapers are now faced with closure as the number of subscriptions decreases and advertising revenue continues to wane. The purpose of this article is to investigate how a newspaper's role is perceived by its local community. This perception is conceptualized as community capital and influences subscription/readership of the newspaper and willingness to visit local retailers that advertise in the newspaper. A midsize local market in the US was surveyed to examine the perceived importance of the newspaper as local community capital with various measurements including readership and advertising impacts. Results suggest that subscribers tend to perceive the newspaper's community capital to be higher than nonsubscribers. Also, subscribers were more likely than nonsubscribers to visit businesses that advertise in the local newspaper.